Renovation of residences from previous historical eras and styles - Погранична, Ірина; Pohranychna, Iryna (Видавництво Львівської політехніки, 2023)
Центральну частину історичних міст формує рядова житлова забудова, яка не відповідає теперішнім архітектурно-функціональним вимогам та будівельним нормам, а тому вимагає комплексної реконструкції. Через це актуальним є питання дослідження типів житлової забудови історичних міст та сучасного стану планувальної структури історичних квартир, що в подальшому дозволить провести фахову реставрацію. Метою даного дослідження було визначити сучасний стан історичної забудови, її архітектурні особливості та запропонувати основні принципи реконструкції житлових будинків різних історичних епох. Під час дослідження було використано загальнонаукові методи дослідження (метод порівняння, метод аналізу) і спеціальні методи: типологічної класифікації, архітектурно-планувального, об’ємно-просторового, стилістичного і ретроспективного аналізу та графічного зіставлення. Встановлено, що в сучасній міській забудові сьогодні існує значна частка житлових будинків з попередніх історичних епох і стилів, які складаються з: окремо розташованих міських садиб з власним подвір’ям, будинків рядової вуличної забудови в 2-4 поверхи з внутрішніми дворами, офіцинами і в’їзними брамами, багатоповерхових будинків тощо. Окремо розташовані міські садиби зараз втратили свою первісну функцію житла і переважно використовуються як громадські об’єкти. Житлові будинки вуличної рядової забудови мають ряд недоліків, від хаотичного перепланування квартир з входом до санвузлів через кухні чи формування темних кімнат, до втрати конструктивної стійкості об’єктів. Саме тому для підвищення рівня комфорту існуючих квартир в житлових будинка з попередніх історичних епох доцільно розробляти комплексні програми з реконструкції такого типу житла. Практична цінність даного дослідження полягає в тому, що рекомендації щодо реконструкції та збереження житлових будинків з попередніх історичних епох можуть бути використані під час реконструкції існуючих житлових будинків в центральних історичних містах України, а також враховані в стратегіях відбудови житлової забудови після завершення російсько-української війни.

The central part of historic cities is developed by ordinary residential buildings that do not correspond to the current architectural and functional requirements and building codes, and therefore require comprehensive reconstruction. Therefore, it is essential to explore the types of residential development in historic cities and the current state of the planning structure of historic apartments, which will allow for professional restoration in the future. The purpose of this research was to determine the current state of historic buildings, and their architectural features, and to propose the basic principles of reconstruction of residential buildings of different historical eras. The research used general scientific research methods (method of comparison, method of analysis) and special methods: typological classification, architectural and planning, three-dimensional, stylistic and retrospective analysis, and graphic comparison. It has been established that in modern urban development today there is a significant share of residential buildings from previous historical eras and styles, consisting of: detached urban estates with their courtyard, ordinary street buildings of 2-4 floors with courtyards, offices and entrance gates, multi-storey buildings, etc. Detached urban estates have now lost their original function as housing and are mainly used as public facilities. Residential buildings of street-level construction have several disadvantages, from the chaotic redevelopment of apartments with access to bathrooms through kitchens or the development of dark rooms to the loss of structural stability of the buildings. Thus, to improve the comfort level of existing apartments in residential buildings from previous historical eras, it is advisable to develop comprehensive programmes for the reconstruction of this type of housing. The practical value of this research is that the recommendations for the reconstruction and preservation of residential buildings from previous historical eras can be used in the reconstruction of existing residential buildings in the central historical cities of Ukraine, and considered in strategies for the reconstruction of residential buildings after the end of the Russian-Ukrainian war.
Реконструкція житлових будинків з попередніх історичних епох і стилів
Keywords: житлова рядова забудова; перепланування; планувальна структура; стратегія розвитку; residential row housing; redevelopment; planning structure; development strategy; 728